ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN UMKM DI KECAMATAN MOROTAI SELATAN - Lukman Wangko; Nurdin Natan (Peneliti.net, 2026)
This study aims to determine the effect of: (1). Does the capital factor affect the income of MSMEs in South Morotai District, (2). Does the labor factor affect the income of MSMEs in South Morotai District, (3). Does the education factor affect the income of MSMEs in South Morotai District, (4). Does the working hour factor affect the income of MSMEs in South Morotai District. This study used a questionnaire to obtain data. The population of this study were 50 MSME actors. The research method used is quantitative method using SPSS V31 to process the data obtained. The results show (1) capital has a positive and significant effect on business income, with a sig. 0,002< 0,05. . This means that the existence of MSME capital will increase MSME income in South Morotai District. (2) labor also has a positive and significant effect on income with a sig. 0,047<0,05. Based on the results of hypothesis testing, it is concluded that if the presence of labor by an MSME will not affect business income in South Morotai District. (3) if education has a positive but insignificant effect on income with sig. 0,001>0,05. So it is concluded that with education in an MSME, it can increase the business income of an MSME in South Morotai District. (4) if working hours have a positive and significant effect on income with a sig value. 0,003<0,05. So it is concluded that by scheduling working hours in an MSME, it can increase the business income of an MSME in South Morotai District. And finally (5) if business capital, labor, education, and working hours are simultaneously positively and significantly influenced with a sig. 0.001 <0.05 on business income in South Morotai District. Therefore, it is concluded that MSME business income in South Morotai District is influenced by business capital, labor, education, and working hours. This will have an impact on the local economy.